2012
DOI: 10.1590/s0100-736x2012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Surtos de infecção por Piscinoodinium pillulare e Henneguya spp. em pacus (Piaractus mesopotamicus) criados intensivamente no Sudoeste de Goiás

Abstract: Três surtos de infecção por Piscinoodinium pillulare e Henneguya spp. em Piaractus mesopotamicus criados intensivamente no Sudoeste de Goiás são descritos. Dois surtos ocorreram no inverno e um no verão. As taxas de morbidade (58,57%-90%) e mortalidade (100%) foram determinadas. Episódios de estresse ocorreram previamente em todos os casos. Sinais clínicos incluíam mudanças comportamentais e movimentos erráticos com perda de equilíbrio. Os principais achados macroscópicos foram tumefação das brânquias com exsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(30 reference statements)
1
4
1
10
Order By: Relevance
“…However, the observed rates of infection were lower than those described for tambacu farmed in different regions other than the Brazilian Southeast (Tavares-Dias et al, 2001a;Schalch & Moraes, 2005), and were also lower than reports of P. mesopotamicus in the Central-West region (Sant'Ana et al, 2012), where this protozoan caused high mortality. Martins et al (2001) reported a mortality of 61.3% in the winter season (May-August) in the Southeast region, when water temperatures ranged from 17 to 24 o C. In the Central-West region, this protozoan occurred in winter and summer, and 100% of mortality was observed by Sant'Ana et al (2012). However, no mortality has been recorded in fish farmed in the Amazon region.…”
Section: Resultscontrasting
confidence: 67%
“…However, the observed rates of infection were lower than those described for tambacu farmed in different regions other than the Brazilian Southeast (Tavares-Dias et al, 2001a;Schalch & Moraes, 2005), and were also lower than reports of P. mesopotamicus in the Central-West region (Sant'Ana et al, 2012), where this protozoan caused high mortality. Martins et al (2001) reported a mortality of 61.3% in the winter season (May-August) in the Southeast region, when water temperatures ranged from 17 to 24 o C. In the Central-West region, this protozoan occurred in winter and summer, and 100% of mortality was observed by Sant'Ana et al (2012). However, no mortality has been recorded in fish farmed in the Amazon region.…”
Section: Resultscontrasting
confidence: 67%
“…This same parasite was reported in Cichlasoma amazonarum and in Hemibrycon surinamensis of the Igarapé of Fortaleza basin, Macapá, with a prevalence of 49% and 17.2%, respectively (CARVALHO et al, 2017;HOSHINO et al 2014;HOSHINO et al, 2014). Piscinoodinium pillulare is common in cold season of the year and is responsible for outbreaks in aquaculture, which may cause discomfort and asphyxia in hosts, as described by SANT'ANA et al (2012).…”
Section: Resultssupporting
confidence: 68%
“…As maiores prevalências encontradas foram para os parasitos Monogeneas e Myxobolus sp. A infecção por Monogeneas corrobora os registros em tambaquis em que altas prevalências foram encontradas (95%) em tambaquis cultivados na região Norte, especificamente no estado do Amapá (Santos et al, 2013). Já o protozoário Myxobolus sp.…”
Section: Resultsunclassified
“…(Eiras et al, 2010). Na região do Baixo São Francisco, a fauna parasitária do tambaqui apresentou 10 táxons distintos, podendo, então, ser considerada uma fauna diversa, com um maior número de táxons quando comparada com estudos da região Norte, como nos estados do Amazonas (n= 9 táxons identificados) (Fischer et al, 2003), Amapá (n= 5) (Santos et al, 2013) e Roraima (n= 7) (Godoi et al, 2012).…”
Section: Methodsunclassified
See 1 more Smart Citation